2000
DOI: 10.1034/j.1600-0404.2000.101004262x./
|View full text |Cite
|
Sign up to set email alerts
|

Neurological findings in complex regional pain syndromes - analysis of 145 cases

Abstract: Early diagnosis is a prerequisite for a successful treatment of complex regional pain syndrome (CRPS). In order to describe neurological symptoms which characterize CRPS, we evaluated 145 patients prospectively. Two-thirds of these were women, the mean age at time of investigation was 50.4 years. CRPS followed limb trauma, surgery and nerve lesion. Employing the current IASP criteria 122 patients were classified as CRPS I and 23 as CRPS II. All patients were assessed clinically pain was quantified using the Mc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

8
188
0
21

Year Published

2001
2001
2017
2017

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 297 publications
(217 citation statements)
references
References 23 publications
8
188
0
21
Order By: Relevance
“…This heightened level of spontaneous firing may also indicate that there was ongoing or non-evoked discomfort in the animal because higher levels of WDR activity code for increased somatosensory intensity. Non-evoked pain is observed in the majority of patients with chronic pain and is a primary reason for seeking medical care (Birklein et al, 2000;Backonja and Stacey, 2004). There have been recent advances in measuring nonevoked pain in animals, but this is still a difficult endpoint to accurately assess (King et al, 2009;Langford et (2006) have reported that heightened spontaneous discharges of WDR neurons are either reduced or unaltered by drugs that are effective or ineffective, respectively, in treating non-evoked pain in humans.…”
Section: Downloaded Frommentioning
confidence: 99%
“…This heightened level of spontaneous firing may also indicate that there was ongoing or non-evoked discomfort in the animal because higher levels of WDR activity code for increased somatosensory intensity. Non-evoked pain is observed in the majority of patients with chronic pain and is a primary reason for seeking medical care (Birklein et al, 2000;Backonja and Stacey, 2004). There have been recent advances in measuring nonevoked pain in animals, but this is still a difficult endpoint to accurately assess (King et al, 2009;Langford et (2006) have reported that heightened spontaneous discharges of WDR neurons are either reduced or unaltered by drugs that are effective or ineffective, respectively, in treating non-evoked pain in humans.…”
Section: Downloaded Frommentioning
confidence: 99%
“…3) [42][43][44], and epidemiological studies finding no association with psychopathology [45,46]. As CRPS resolves, which it usually does even without treatment [47], the edema, temperature changes, hyperhidrosis, and abnormal hair growth usually resolve before the pain [48,49], so late-stage patients often no longer meet diagnostic criteria for CRPS but only for posttraumatic neuralgia, demonstrating that these are on a continuum (Fig. 4).…”
Section: Complex Regional Pain Syndromementioning
confidence: 99%
“…Chronic pain is often associated with spontaneous pain (pain in the absence of external stimuli), as well as changes in sensitivity to various somatosensory stimuli (Tasker et al, 1991;Clauw et al, 1999;Sindrup et al, 1999;Birklein et al, 2000;Dworkin, 2002). Approximately 10% of adults have severe chronic pain (Harstall and Ospina, 2003) and CBP is the largest contributor to this population (Atkinson, 2004).…”
Section: Introductionmentioning
confidence: 99%